Ankle muscle coactivation and its relationship with ankle joint kinematics and kinetics during gait in hemiplegic patients after stroke. (2nd April 2016) - Kitatani, Ryosuke; Ohata, Koji; Sato, Shuhei; Watanabe, Aki; Hashiguchi, Yu; Yamakami, Natsuki; Sakuma, Kaoru; Yamada, Shigehito
Abstract: Introduction: Increased ankle muscle coactivation during gait is a compensation strategy for enhancing postural stability in patients after stroke. However, no previous studies have demonstrated that increased ankle muscle coactivation influenced ankle joint movements during gait in patients after stroke. Purpose: To investigate the relationship between ankle muscle coactivation and ankle joint movements in hemiplegic patients after stroke. Methods: Seventeen patients after stroke participated. The coactivation index (CoI) at the ankle joint was calculated separately for the first and second double support (DS1 and DS2, respectively) and single support (SS) phases on the paretic and non-paretic sides during gait using surface electromyography. Simultaneously, three-dimensional motion analysis was performed to measure the peak values of the ankle joint angle, moment, and power in the sagittal plane. Ground reaction forces (GRFs) of the anterior and posterior components and centers of pressure (COPs) trajectory ranges and velocities were also measured. Results: The CoI during the SS phase on the paretic side was negatively related to ankle dorsiflexion angle, ankle plantarflexion moment, ankle joint power generation, and COP velocity on the paretic side. Furthermore, the CoI during the DS2 phase on both sides was negatively related to anterior GRF amplitude on each side. Conclusion: Increased ankle muscle coactivation is related to decreased ankle joint movement during the SS phase on the paretic side to enhance joint stiffness and compensate for stance limb instability, which may be useful for patients who have paretic instability during the stance phase after stroke.